Slag formation during combustion of biomass fuels with low phosphorus content - Öhman, Marcus; Gilbe, Carl; Näzelius, Ida-Linn; Hedman, Henry; Boström, Dan; Boman, Christoffer; Backman, Rainer (Luleå tekniska universitet, Energivetenskap, 2011)
Slag and ash deposition problems have more than occasionally been observed in biomass fueled plants in general and especially in pellet fired plants. These problems can lead to reduced accessibility as well as performance of the combustion appliances. Slag formation including ash transformation mechanisms, measures for prevention and prediction during combustion of biomass fuels has been studied by the research groups at Luleå University of Technology, Umeå University and Energy Technology Center for over one decade now. Several (about 40) different biomass fuels/fuel mixtures have been studied and many different fuel additives/co-combustion fuels have been used to combat slag formation. About 20 scientific papers and 10 technical reports have been published by the research groups within the topic of slag formation during combustion of biomass fuels with low phosphorus content. The objective of the present work was to summarize the general experiences and conclusions of our research within the area of slag formation during combustion of fuels with low phosphorus and varying silicon content. Silicon rich fuels, i.e. fuel ash dominated by silicate-alkali chemistry (e.g. straw fuels), generally shows relatively high slagging tendencies. Exceptions to these general trends exists i.e. fuels with very high Si/K-ratios. Wood derived fuels with a relatively low inherent silicon content shows low or relatively moderate slagging tendencies. However, severe contamination of sand material to woody biomass fuels may greatly enhance the slagging tendencies. Fuel additive addition to problematic woody biomass and straw significantly reduces the slagging tendencies. When adding limestone and kaolin to the problematic wood and straw fuels the composition of the formed slag is changed from relatively low temperature melting silicates to high temperature melting silicates and oxides. The standard ash fusion tests and chemical equilibrium calculations gives useful qualitatively information of the slagging tendencies. However, both ...